If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(6 + 4k) = 23 (6 * -9 + 4k * -9) = 23 (-54 + -36k) = 23 Solving -54 + -36k = 23 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -36k = 23 + 54 Combine like terms: -54 + 54 = 0 0 + -36k = 23 + 54 -36k = 23 + 54 Combine like terms: 23 + 54 = 77 -36k = 77 Divide each side by '-36'. k = -2.138888889 Simplifying k = -2.138888889
| x+35=130 | | x-5x^2= | | d=mb+gaforb | | f(3)=4g+6 | | (3f+6)(2f-4)=0 | | -12n-n=11n-1 | | 5y-8=5y-8 | | F(x)=2x^2+6x+5 | | 7v-17=v+7 | | 6x+20=98 | | 3x+10=8x+15 | | -16t^2-10t+3=0 | | 5x+7=130 | | 7b-66=b | | F(x)=3x^2-4x-2 | | x/69=89 | | x[2x]=24 | | 4x-20=6x | | (5+u)(5u-3)=0 | | a^2-28a+14=-192 | | 24+-5x=7x | | x^2-28a+192=0 | | 8x+5=7x+5 | | -3x+2=1x+10 | | u+13=2u | | 180d=40r+t | | n--7.6=8.9 | | 11x-x=0 | | 4/5x1and1/6 | | y=390+11(x) | | 24=72t-16t^2 | | 5x-4=6x+3 |